Peningkatan Motorik Kasar Anak Melalui Kegiatan Bermain Lempar Tangkap Bola - Pipit Fitriani; Joni Joni; Nurmalina Nurmalina (Jurnal Pendidikan Tuntas, 2023)
The low gross motor skills of children in group A of Permata Bunda Kindergarten as reason for this research, while one of the solutions offered by researchers was the apply of throwing and catching balls activities. The type of research applied was classroom action research with 2 cycles and 2 meetings in each cycle. Data collection techniques used are observation techniques and documentation techniques. The results of the research was that the gross motor skills of group A children in Kindergarten Permata Bunda, Banjar Panjang Village, Kerumutan District, Pelalawan Regency could be improved through throwing and catching balls. The increase that occurs can be seen from the research stage, namely observations made during pre-action, implementation of cycle I and cycle II actions. Judging from the results of the pre-action with ball throwing activities, the value for the BB criteria is the number of children 14 with a percentage of 70%, the BM criteria the number of children is 4 with a percentage of 20%, in the BSH criteria the number of children is 2 the percentage is 10% and in the BSB criteria the number of children is 0 percentage 0 %. In the first cycle of throwing activities, the criteria for BB number of children is 1 percentage 5%, BM number of children is 3 percentage 15%, BSH number of children is 15 percentage 75% and BSB number of children is 1 percentage 5%. In the activity of catching the BB criteria the number of children is 0 percentage 0%, BM the number of children is 4 percentage 20%, BSH the number of children is 12 the percentage is 60% and BSB the number of children is 4 percentage 20% In cycle II the following data were obtained on Throwing activities with BB criteria number of children 0 percentage 0%, BM number of children 1 percentage 5%, BSH number of children 3 percentage 15%. BSB number of children 16 percentage 80%. In the activity of catching the criteria for BB the number of children is 0 percentage 0%, BM the number of children is 1 percentage 5%, BSH the number of children is 4 the percentage is 20% and BSB the number of children is 15 the percentage is 75%. From the data above, the implementation of actions in cycle I to cycle II shows that the acquisition of children has increased, namely in throwing activities, throwing activities from 1 or 5% to 16 or 80%, while catching activities the number of children is 4 or 20% to 15 or 75%. Keywords: Gross Motor, throwing and catching, Classroom Action Research